Laser Resurfacing - Janik, Joseph P. (Thieme Medical Publishers, 2007)
In a society desiring images of beauty and youthfulness, the world of cutaneous surgery offers the gifts of facial rejuvenation for those determined to combat the signs of aging. With the development of novel laser and plasma technology, pigmentary changes, scarring, and wrinkles can be conquered providing smoother, healthier, younger-looking skin. This review highlights five of the most popular resurfacing technologies in practice today including the carbon dioxide (CO(2)) laser, the erbium:yttrium-aluminum-garnet (Er:YAG) laser, combination resurfacing, fractional photothermolysis, and plasma resurfacing.